OTOMASI SISTEM GREENHOUSE BERBASIS MIKROKONTROLER - Al Gaufiqy, Muh Harist; Rasmana, Susijanto Tri; Puspasari, Ira (Journal of Control and Network Systems (JCONES), 2017)
Greenhouse (Greenhouse) is a home or building which large scale or small made by paranet, glass, plastic UV Filter for filter light entering the greenhouse, the function of the greenhouse are abele to monitor the temperature and humidity, monitoring, lighting and watering plants automatically ,for generally implants in the greenhouse are hydroponic plants. For urban areas that have hot temperatures and low humidity obviously, for this condition greenhouse can be a solution to control temperature and humidity. In this study the greenhouse system that regulates the temperature and humidity of the room according to the needs of the plant. The system is flexible for setting point in accordance with the terms of the temperature and humidity range of plants. Actucator used is chasing the fan 12 V DC, waterpump and humidifier are controlled by on off system with the time of the achievement of set point for temperature and humidity parameters. Based on the results of the final test on this study to decrease the temperature of 1oC-3oC which tested as many as 30 times with an average error percentage 1,12%. And for testing the moisture percentage error of 0% with increasing humidity up to 30%.Humidity oversoot data reaches 12%. And for temperature is bale to decrease 1oC only. Average time overshoot occurs within 4 minutes. Average time rise time humidity occurs within 3 minutes, the average time settling time humidity occurs within 3 minutes 30 seconds. For the highest overshoot temperature is 1oC. The average time the temperature overshoot occurs in a duration of 4 minutes 70 seconds, the average time temperatures rise time occurs within the duration of 5 minutes 50 seconds, an average settling time temperature occurs within 3 minutes. Keyword:Greenhouse otomation, DHT11, Humidifier, Microcontroller